THE ROLE OF PERSUASIVE COMMUNICATION OF INDEPENDENT KITCHEN MANAGERS ABOUT THE BENEFITS OF FREE NUTRITIONAL MEALS (MBG) IN KARYA MULYA VILLAGE, KESAMBI DISTRICT, CIREBON CITY - Sanjaya, Izzi Yekli (Management Studies and Business Journal (PRODUCTIVITY), 2025)
Nutritional problems in Indonesia remain a major challenge in the development of a healthy and productive human resource base. The Free Nutritious Meal Program ( MBG), implemented by Dapur Independent in the Village Karya Mulya, Kesambi District, Cirebon City, serves as one of the efforts to address this issue. This study aims to analyze the role of persuasive communication by Dapur Mandiri administrators in conveying the benefits of the MBG program to the community. This research employed a quantitative method with a survey approach involving 31 program beneficiaries. Data were collected using a Likert-scale questionnaire. The results show that persuasive communication — characterized by the use of easily understood language, a friendly approach, clear information delivery, and community involvement in evaluation — significantly contributed to the program's effectiveness. The majority of respondents indicated that the information provided increased their trust in the program, raised their nutritional awareness, and improved coordination and service organization. These findings highlight the critical role of persuasive communication in enhancing community participation and the success of nutrition-based social programs.